Vertical Integration and Service Orchestration for Modular Production Systems Using Business Process Models. (2016) - Wrede, Sebastian; Beyer, Oliver; Dreyer, Christoph; Wojtynek, Michael; Steil, Jochen
Abstract: Individualized production challenges established manufacturing approaches in terms of modularization, flexibility and efficient reconfiguration. Modular production systems with high flexibility, capable of interacting with products and humans, and vertically integrated with the business environment provide new possibilities for overcoming these challenges. Such flexible manufacturing approaches require seamless integration between all involved parties from the enterprise resource planning level down to the shop floor. Service-oriented architectures with standards geared towards automation claim to provide easier development and integration of modular production systems. However, in order to support the desired flexibility and integrability, a coherent modeling approach for manufacturing processes is required, in particular focusing on the orchestration between production tasks, resources, humans and services. To address these challenges, we introduce in this contribution a system-level approach for flexible manufacturing comprised of reconfigurable modular production cells, which can be easily composed into production lines. Reconfigurability is achieved through exchangeable process components, the use of lightweight robot manipulators as versatile handling subsystems as well as a cell control scheme based on executable business process models to allow runtime service orchestration. The systemic approach can be applied to realize a customer specific production down to lot size one and was validated in a vertically integrated production line manufacturing an industrial product with high variability. The resulting system has been exhibited at different trade fairs and demonstrates our interpretation of the SmartFactory paradigm for individualized production.